Method for preparing sulfur heteroatom doped multi-channel hollow oxygen-enriched carbon nanorod

By preparing sulfur heteroatom doped multi-channel hollow oxygen-rich carbon nanorods and applying them to lithium-sulfur battery separators, the problem of self-discharge effect of lithium-sulfur batteries is solved, and the rate performance and long-term circulation performance of the battery are significantly improved.

CN119841306APending Publication Date: 2025-04-18YULIN NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510009410.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The self-discharge effect of lithium-sulfur batteries is significant, mainly due to the dissolution and diffusion of polysulfides in the electrolyte, which causes the lithium negative electrode to react with polysulfides, causing rapid attenuation of battery capacity and low Coulomb efficiency.

Method used

A method of preparing sulfur heteroatom-doped multi-channel hollow oxygen-rich carbon nanorods is adopted to prepare sulfur-doped hollow oxygen-rich carbon nanorods through pretreatment, solvent-thermal reaction, preoxidation, calcination and grinding steps, and is applied to the separator field of lithium-sulfur batteries to suppress the self-discharge effect.

Benefits of technology

The hollow oxygen-rich carbon nanorod doped with sulfur heteroatoms can effectively suppress the shuttle effect of lithium polysulfide, significantly reduce the self-discharge effect of lithium sulfur batteries, and improve the battery's rate performance and long-term charge and discharge cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841306A_ABST
    Figure CN119841306A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material science, in particular to a method for preparing a sulfur heteroatom doped multi-channel hollow oxygen-enriched carbon nanorod, which comprises the following steps: by taking sisal fibers as a raw material, cleaning and drying, adding a mixed solution of lipoic acid, ethanol and secondary water, soaking the sisal fibers for 24 hours, transferring to perform solvothermal reaction, and drying to obtain the sulfur heteroatom doped multi-channel hollow oxygen-enriched carbon nanorod. Cleaning and drying a solvothermal product, pre-oxidizing the solvothermal product in a muffle furnace at the temperature of 300 DEG C, transferring the pre-oxidized solvothermal product into a tubular furnace, calcining the pre-oxidized solvothermal product in an argon atmosphere at the calcining temperature of 700-1000 DEG C at the heating rate of 10 DEG C / min for 4 hours, cooling the pre-oxidized solvothermal product to room temperature, and grinding the calcined product into powder for about 30 minutes by using an agate mortar, so as to obtain the sulfur-doped hollow oxygen-enriched carbon nanorod. The sulfur-doped hollow oxygen-enriched carbon nanorod is applied to the field of lithium-sulfur battery diaphragms, and it is found that the heteroatom-doped hollow oxygen-enriched carbon nanorod can effectively inhibit the shuttle effect of lithium polysulfide and inhibit the self-discharge effect of a lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material science, and in particular to a method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods. Background Art

[0002] Lithium-sulfur battery is a type of lithium-ion battery. It uses sulfur as the positive electrode and metallic lithium as the negative electrode. Elemental sulfur is abundant in the earth and has the characteristics of low price and environmental friendliness. Lithium-sulfur battery using sulfur as the positive electrode material has high material theoretical specific capacity and battery theoretical specific energy density, reaching 1675mAh / g and 2600Wh / kg respectively, which is much higher than the capacity of lithium cobalt oxide battery widely used in commercial applications (<150mAh / g). Sulfur is an environmentally friendly element with little pollution to the environment, and is a very promising lithium battery.

[0003] However, the self-discharge effect of lithium-sulfur batteries is particularly significant, mainly due to the dissolution and diffusion of polysulfides (LiPS) in the electrolyte, which causes them to react with the lithium negative electrode, resulting in rapid decay of battery capacity and low Coulombic efficiency. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing sulfur heteroatom-doped multi-channel hollow oxygen-rich carbon nanorods, and to apply the sulfur heteroatom-doped hollow oxygen-rich carbon nanorods to the field of lithium-sulfur battery separators to suppress the self-discharge effect of lithium-sulfur batteries.

[0005] To achieve the above object, the present invention provides a method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods, comprising the following steps:

[0006] Step 1: Select sisal fiber for pretreatment;

[0007] Step 2: preparing a mixed solution of lipoic acid, ethanol and secondary water, soaking the sisal fiber and transferring it to perform a solvothermal reaction;

[0008] Step 3: washing and drying the solvent thermal product and then pre-oxidizing it;

[0009] Step 4: calcining the pre-oxidized product;

[0010] Step 5: Grind the calcined product into powder using an agate mortar for about 30 minutes to obtain sulfur-doped hollow oxygen-rich carbon nanorods.

[0011] Optionally, the execution process of step 1 is specifically to wash the sisal fiber with secondary water and ethanol for more than three times, and then dry it at 100° C. in a constant temperature blast drying oven under air atmosphere.

[0012] Optionally, during the execution of step 2, 0.1-1.0 g of lipoic acid is added to a mixed solution of 70-120 mL of ethanol and secondary water, and stirred to completely dissolve it. Then, 12-20 g of sisal fiber is added to the above solution, and after soaking for 24 hours, the solution is transferred to a high-pressure reactor and subjected to solvent thermal reaction at 200° C. in a constant temperature forced air drying oven for 24 hours.

[0013] Optionally, in step 3, the obtained product is washed with secondary water and ethanol three times each, and then placed in a vacuum drying oven for vacuum drying at 60° C. for 12 h, and the dried solvent thermal product is placed in a muffle furnace for pre-oxidation at 300° C. for 5 h.

[0014] Optionally, the execution process of step 4 is specifically to transfer the pre-oxidized product to a tubular furnace and calcine it under an argon atmosphere at a calcination temperature of 700-1000°C, a heating rate of 10°C / min, calcination for 4 hours, and cooling to room temperature after calcination.

[0015] The present invention provides a method for preparing sulfur heteroatom doped multi-channel hollow oxygen-rich carbon nanorods, using sisal fiber as a raw material, adding a mixed solution of thioctic acid, ethanol and secondary water after washing and drying, transferring the sisal fiber for solvent thermal reaction after soaking for 24 hours, then washing and drying the solvent thermal product, placing it in a muffle furnace at 300°C for pre-oxidation, and then transferring it to a tubular furnace and calcining it in an argon atmosphere, the calcination temperature is 700-1000°C, the heating rate is 10°C / min, the calcination is 4h, and the calcination is completed. After cooling to room temperature, the calcined product is ground into powder with an agate mortar for about 30min, and sulfur-doped hollow oxygen-rich carbon nanorods are obtained. The sulfur-doped hollow oxygen-rich carbon nanorods of the present invention are applied to the field of lithium-sulfur battery separators, and it is found that the heteroatom-doped hollow oxygen-rich carbon nanorods can effectively inhibit the shuttle effect of lithium polysulfide and inhibit the self-discharge effect of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 The present invention is a schematic flow chart of the steps of a method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods.

[0018] Figure 2 3 are scanning electron microscope images of different resolutions of sulfur heteroatom-doped hollow oxygen-rich carbon nanorods in a specific embodiment of the present invention.

[0019] Figure 3 It is a transmission electron microscope image and an element dispersion image of the sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods in a specific embodiment of the present invention.

[0020] Figure 4 It is a schematic diagram of the rate performance test of a lithium-sulfur battery assembled using a polyolefin separator in a specific embodiment of the present invention.

[0021] Figure 5 It is a schematic diagram of the self-discharge performance test of a lithium-sulfur battery assembled using a polyolefin separator after being left for 14 days in a specific embodiment of the present invention.

[0022] Figure 6 It is a schematic diagram comparing the cycle performance of lithium-sulfur batteries using a polyolefin separator in a specific embodiment of the present invention and using the barrier film of the present invention. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0024] See also Figure 1 The present invention provides a method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods, comprising the following steps:

[0025] S1: sisal fiber is selected for pretreatment;

[0026] S2: preparing a mixed solution of lipoic acid, ethanol and secondary water, soaking the sisal fibers and transferring them for solvothermal reaction;

[0027] S3: washing and drying the solvent thermal product and then pre-oxidizing it;

[0028] S4: calcining the pre-oxidized product;

[0029] S5: Grind the calcined product into powder using an agate mortar for about 30 minutes to obtain sulfur-doped hollow oxygen-rich carbon nanorods.

[0030] The execution process of step 1 is specifically to wash the sisal fiber with secondary water and ethanol for more than three times, and then dry it at 100° C. in a constant temperature blast drying oven under air atmosphere.

[0031] During the execution of step 2, 0.1-1.0 g of lipoic acid is added to a mixed solution of 70-120 mL of ethanol and secondary water, and stirred to completely dissolve it. Then, 12-20 g of sisal fiber is added to the above solution, and after soaking for 24 hours, it is transferred to a high-pressure reactor and subjected to solvent thermal reaction at 200° C. in a constant temperature forced air drying oven for 24 hours.

[0032] In step 3, the obtained product is washed with secondary water and ethanol three times respectively, and then placed in a vacuum drying oven for vacuum drying at 60° C. for 12 h. The dried solvent thermal product is placed in a muffle furnace for pre-oxidation at 300° C. for 5 h.

[0033] The execution process of step 4 is specifically to transfer the pre-oxidized product to a tubular furnace and calcine it in an argon atmosphere at a calcination temperature of 700-1000°C, a heating rate of 10°C / min, calcination for 4 hours, and cooling to room temperature after calcination.

[0034] Further, in order to illustrate the benefits of the present invention, the present invention proposes a specific embodiment, please refer to Figures 2 to 6 The sulfur heteroatom-doped multi-channel hollow oxygen-rich carbon nanorods of the present invention are used in the self-discharge test of lithium-sulfur batteries.

[0035] The specific process is as follows:

[0036] Preparation of lithium-sulfur battery separator: Sulfur atom-doped hollow oxygen-rich carbon nanorods, conductive carbon and binder are dispersed in N-methylpyrrolidone in a ratio of 8:1:1 and stirred for 6 to 8 hours until a uniform slurry is obtained. The slurry is then coated on the surface of the commercial separator with a scraper and dried in a vacuum drying oven at 60°C for 12 hours before cutting into pieces. The obtained separator is used to assemble CR2032 button batteries and the electrochemical properties are tested.

[0037] Assembly of CR2032 button cell: The structure of CR2032 button cell from bottom to top consists of negative electrode shell, lithium sheet, lithium-sulfur battery separator, C / S electrode, gasket, shrapnel, and positive electrode shell. In a glove box with argon atmosphere, first place the lithium sheet on the negative electrode shell, use a pipette to drip 20μL of lithium-sulfur electrolyte in the center of the lithium sheet, then place the above lithium-sulfur battery separator on the lithium sheet, and then use a pipette to drip 20μL of lithium-sulfur electrolyte, put the C / S electrode in, and then put the gasket and shrapnel in turn, cover the positive electrode shell, and finally put the assembled battery into the button battery sealing machine for sealing, and wait for 10s before taking it out of the sealing machine.

[0038] Lithium-sulfur battery test procedure: Use Shenzhen Xinwei New Energy BTS 4000 battery test system to place the battery in the test window of a 30℃ constant temperature box, and test the charge and discharge rate performance of the lithium-sulfur battery with a charge and discharge voltage of 1.7-2.8V and constant current mode. At a constant temperature of 30℃ and a charge and discharge voltage window of 1.7-2.8V, set the constant current mode to charge and discharge once and then set aside for 14 days, and then continue to test the long-term charge and discharge cycle performance of the battery.

[0039] In the experiment Figure 2 Shown are scanning electron microscope images of prepared sulfur atom-doped hollow oxygen-rich carbon nanorods at different resolutions. From the images, it can be seen that the carbon material has hollow channels with different channel pore sizes. Figure 3 The transmission electron microscope image and element dispersion diagram of the hollow oxygen-rich carbon nanorods doped with sulfur atoms. The hollow structure of the nanorods can be seen from the transmission electron microscope image, and the carbon material has an amorphous structure. The transmission electron microscope element dispersion diagram shows that the hollow nanorods have carbon, oxygen and sulfur elements, indicating the successful preparation of the hollow oxygen-rich carbon nanorods doped with sulfur atoms. Figure 4 The rate performance test of lithium-sulfur batteries assembled with polyolefin separators and polyolefin separators modified with sulfur heteroatom-doped hollow oxygen-rich carbon nanorods shows that the discharge specific capacities of polyolefin separator batteries at current densities of 0.2C, 0.5C, 1C, 2C, 3C, 4C, 5C, 6C, 7C, 8C, 9C, and 10C are 867.86 mAh g -1 、737.50mAh·g -1 、674.58mAh·g -1 、611.73mAh·g -1 、558.06mAh·g -1 、481.56mAh·g -1 、440.02mAh·g -1 、386.33mAh·g -1 、357.81mAh·g -1 、164.97mAh·g -1 、147.88mAh·g -1 、134.52mAh·g -1 The discharge specific capacities of the sulfur-doped hollow oxygen-rich carbon nanorod-modified polyolefin separator battery at 0.2C, 0.5C, 1C, 2C, 3C, 4C, 5C, 6C, 7C, 8C, 9C, and 10C were 1188.08 mAh·g -1 、1060.08mAh·g -1 、996.13mAh·g -1 、917.14mAh·g -1、851.96mAh·g -1 、802.72mAh·g -1 、756.22mAh·g -1 、734.45mAh·g -1 、696.55mAh·g -1 、681.36mAh·g -1 、622.85mAh·g -1 、567.79mAh·g -1 Compared with the discharge capacity of the two batteries, the polyolefin separator battery modified by sulfur atom-doped hollow oxygen-rich carbon nanorods showed better rate performance. The discharge capacity was higher than that of the polyolefin separator battery at different current densities, indicating that sulfur atom-doped hollow oxygen-rich carbon nanorods had a significant effect on improving the conversion of lithium polysulfide, inhibiting the shuttling of lithium polysulfide and obtaining better rate performance.

[0040] Figure 5 In order to test the self-discharge of lithium-sulfur batteries assembled with polyolefin separators and polyolefin separators modified with hollow oxygen-rich carbon nanorods doped with sulfur atoms, after two weeks of storage, the self-discharge efficiency of the battery assembled with polyolefin separators modified with hollow oxygen-rich carbon nanorods doped with sulfur atoms was only 8.12%, which was much lower than the 51.8% of commercial polyolefin separators, proving that hollow oxygen-rich carbon nanorods doped with sulfur atoms can effectively inhibit the shuttling of lithium polysulfide, thereby inhibiting the self-discharge efficiency.

[0041] Figure 6 The lithium-sulfur battery assembled with polyolefin separator and polyolefin separator modified with sulfur heteroatom-doped hollow oxygen-rich carbon nanorods was subjected to a long-term charge and discharge cycle test after one charge and discharge in constant current mode and then left for 14 days. The battery after the self-discharge test was subjected to a long-term cycle charge and discharge test with a current density of 0.2C. The discharge specific capacity of the polyolefin separator battery after 700 charge and discharge cycles was 308.59mAh·g -1 , which is much lower than that of the polyolefin separator battery modified by sulfur heteroatom-doped hollow oxygen-rich carbon nanorods (457.21 mAh g -1 The discharge specific capacity of the sulfur atom-doped hollow oxygen-rich carbon nanorod-modified polyolefin separator battery can still maintain a high performance after multiple charge and discharge cycles, indicating that the sulfur atom-doped hollow oxygen-rich carbon nanorod-modified polyolefin separator has a strong adsorption effect on lithium polysulfide, inhibiting the shuttle effect of lithium polysulfide, thereby reducing the self-discharge effect.

[0042] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods, characterized in that: The following steps are involved: Step 1: Select sisal fiber for pretreatment; Step 2: preparing a mixed solution of lipoic acid, ethanol and secondary water, soaking the sisal fiber and transferring it to perform a solvothermal reaction; Step 3: washing and drying the solvent thermal product and then pre-oxidizing it; Step 4: calcining the pre-oxidized product; Step 5: Grind the calcined product into powder using an agate mortar for about 30 minutes to obtain sulfur-doped hollow oxygen-rich carbon nanorods.

2. The method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods according to claim 1, characterized in that: The execution process of step 1 is specifically to wash the sisal fiber with secondary water and ethanol for more than three times, and then dry it at 100° C. in a constant temperature blast drying oven under air atmosphere.

3. The method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods according to claim 2, characterized in that: During the execution of step 2, 0.1-1.0 g of lipoic acid is added to a mixed solution of 70-120 mL of ethanol and secondary water, and stirred to completely dissolve it. Then, 12-20 g of sisal fiber is added to the above solution, and after soaking for 24 hours, it is transferred to a high-pressure reactor and subjected to solvent thermal reaction at 200° C. in a constant temperature forced air drying oven for 24 hours.

4. The method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods according to claim 3, characterized in that: In step 3, the obtained product is washed with secondary water and ethanol three times respectively, and then placed in a vacuum drying oven for vacuum drying at 60° C. for 12 h. The dried solvent thermal product is placed in a muffle furnace for pre-oxidation at 300° C. for 5 h.

5. The method for preparing sulfur atom-doped multi-channel hollow oxygen-rich carbon nanorods according to claim 4, characterized in that: The execution process of step 4 is specifically to transfer the pre-oxidized product to a tubular furnace and calcine it in an argon atmosphere at a calcination temperature of 700-1000°C, a heating rate of 10°C / min, calcination for 4 hours, and cooling to room temperature after calcination.